Qualitative Study of Determinants of Medical Record Completeness of Inpatients at Dr. Hadrianus Sinaga Hospital in 2023 - Lasrina E. Tambun; Rahmat Alyakin Dachi; Janno Sinaga (Jurnal Info Sains : Informatika dan Sains, 2023)
Medical records are files that contain records and documents about patient identity, examination, treatment, actions and other services that have been provided to patients. Medical records must be kept either electronically or in writing that is clear and concise. Medical record documents that have been completed by the doctor within less then 24 hours after completion of the service or after the inpatient is decided to go home. This research is a qualitative research. The research instrument is the researcher himself who is subjective, so the data obtained is checked for validity using triangulation techniques, namely source triangulation, technical triangulation and time triangulation. Informants are the Doctor in Charge, Nurse, Midwife, Head of Medical Records Installation and hospital management, namely the Head of Nursing and Midwifery Services Section. Interviews were conducted according to Esterberg and literature studies. The results showed that the determinants of the completeness of Medical Record files were influenced by Man, namely the indiscipline in filling out Medical Record files, Machine, namely the absence of a policy from management if human resources was not disciplined in filling out Medical Record files, Method, namely the lack of motivation in filling in accordance with the SOP, Material, namely sometimes slow provision of parts Medical Record dan Money forms, that is there is no reward dan punishment if the Medical Record is complete.